Smart technologies : breakthroughs in research and practice - Information Resources Management Association (Hershey, PA : IGI Global, 2018)
'This book provides a comprehensive interdisciplinary and refereed research on the most emerging and breakthrough areas of information science and technology. Including innovative studies on Image and speech recognition, human-computer interface, and wireless technologies'--
Includes bibliographical references and index.
Keywords: Technological innovations